Antibacterial activity of ethanolic and aqueous extracts of Acacia aroma Gill. ex Hook et Arn - Arias, Myriam Elizabeth (2004)
The purpose of the present study was to investigate the antibacterial activity of seven ethanolic extracts and three aqueous extracts from various parts (leaves, stems and flowers) of A. aroma against 163 strains of antibiotic multi-resistant bacteria. The disc diffusion assay was performed to evaluate antibacterial activity of the A. aroma crude extracts, against several Gram-positive bacteria (E. faecalis, S. aureus, coagulase-negative stahylococci, S. pyogenes, S.agalactiae, S. aureus ATCC 29213, E. faecalis ATCC 29212) and Gram-negative bacteria (E. coli., K.pneumoniae, P. mirabilis, E. cloacae, S. marcescens, M morganii, A. baumannii, P. aeruginosa, S. maltophilia, E. coli  ATCC 35218, P. aeruginosa ATCC 27853, E. coli ATCC 25922). All ethanolic extracts showed activity against gram-positive bacteria. Among all obtained extracts, only leaf and flower fluid extracts showed activity against Gram-negative bacteria. Based on this bioassay, leaf fluid extracts tended to be the most potent, followed by flower fluid extracts. Minimal inhibitory concentration (MIC) values of extracts and antibiotics were comparatively determined by agar and broth dilution methods. Both extracts were active against S. aureus, coagulase-negative stahylococci, E. faecalis and E. faecium and all tested Gram-negative bacteria with MIC values from 0.067 to 0.308 mg/ml. In this study the minimal bactericidal concentration (MBC) values were  identical or twice as high than the corresponding MIC for leaf extracts and four or eight times higher than MIC values for flower extracts. This may indicate a bactericidal effect. Stored extracts have similar antibacterial activity as recently obtained extracts.